2020
DOI: 10.3390/biomedicines8080274
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Arachidonic Acid Remodeling During Phagocytosis in Mouse Peritoneal Macrophages

Abstract: Macrophages contain large amounts of arachidonic acid (AA), which distributes differentially across membrane phospholipids. This is largely due to the action of coenzyme A-independent transacylase (CoA-IT), which transfers the AA primarily from diacyl choline-containing phospholipids to ethanolamine-containing phospholipids. In this work we have comparatively analyzed glycerophospholipid changes leading to AA mobilization in mouse peritoneal macrophages responding to either zymosan or serum-opsonized zymosan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…These cells have been found to contain high amounts of AA in membrane phospholipids; 20–25% of total fatty acid content is AA [ 71 , 72 ]. Importantly, macrophages also exhibit a characteristic distribution of AA among phospholipids, with PE, not PC, constituting the richest AA containing class, and PI containing much lesser amounts than PE or PC [ 18 , 21 ]. Among molecular species, the ethanolamine plasmalogens are markedly enriched with AA [ 56 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells have been found to contain high amounts of AA in membrane phospholipids; 20–25% of total fatty acid content is AA [ 71 , 72 ]. Importantly, macrophages also exhibit a characteristic distribution of AA among phospholipids, with PE, not PC, constituting the richest AA containing class, and PI containing much lesser amounts than PE or PC [ 18 , 21 ]. Among molecular species, the ethanolamine plasmalogens are markedly enriched with AA [ 56 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mouse resident peritoneal macrophages, PE constitutes the major AA-containing class (45–50% of total cellular AA), followed by PC (35–40%), and PI (5–15%) [ 18 , 21 ]. Note that the 3 H/ 14 C ratio for extracellular free AA is considerably higher than that of the prostaglandins, thus suggesting a substantial contribution of PE, in addition to PC and PI, to AA release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eicosanoids are a broad family of oxygenated lipid compounds that include prostaglandins, thromboxanes, and leukotrienes. Eicosanoids are generated via non-enzymatic oxidation of ARA or by the action of enzymes, such as cyclooxygenase (COX), lipooxygenase (LOX), and cytochrome P450 (CYP) ( Dennis and Norris, 2015 ; Gil-de-Gómez et al, 2020 ). Eicosanoids exert immunomodulatory functions and, depending on the species of eicosanoids, can have pro- or anti-inflammatory effects ( Dennis and Norris, 2015 ).…”
Section: Lipid Signaling By Cpla 2 αmentioning
confidence: 99%
“…The inhibition of secretory PLA 2 s (sPLA 2 s) GIIA, GV, and GX or cPLA 2 α did not alter the classically activated macrophage production of eicosanoids, suggesting a select role for iDLs on macrophage polarization. However, other groups have reported a role for sPLA 2 or cPLA 2 α in eicosanoid production from macrophages [ 142 , 143 , 144 , 145 , 146 , 147 ]. Those studies were performed with macrophage-like cells (RAW264.7 and P388D1) or peritoneal macrophages from rats and mice, with only LPS (10-1000 ng/mL) or zymosan stimulation for 6–48 h, and the involvement of various PLA 2 s was discerned with chemical inhibitors, some of which effected multiple PLA 2 s. In contrast, our studies were performed with primary mouse peritoneal macrophages, which have been demonstrated to behave differently from the macrophage-like cells [ 36 ], from wild-type and genetically- modified iPLA 2 β-deficient mice, and importantly, treated with LPS+IFNγ, conditions that induce a M1 macrophage phenotype.…”
Section: Deleterious Impact Of Ipla 2 β Activationmentioning
confidence: 99%